Penerapan Lembar Kerja Murid Rangkai Upaya Peningkatan Keterampilan Menulis dan Sikap Kritis Murid SD Kelas II - Aprilia, Gana Atheeva Teen; Purwati, Panca Dewi (Lembaga Yasin AlSys, 2025)
The Think–Talk–Write (TTW) instructional model has been widely studied; however, research that specifically integrates deep learning supported by the student worksheet Rangkai Lingkungan Rumahku, combined with visual media word cards to enhance critical reasoning attitudes and writing skills among primary school students, remains limited. This study aims to describe the implementation of the TTW model assisted by student worksheets stimulated by visual word card media, and to assess its effectiveness in improving the critical reasoning and writing abilities of third-grade students. A mixed methods approach was employed over two cycles, involving 28 students selected through total sampling. Data were collected using observation sheets, interviews, and student worksheet-based tests (pretest–posttest), and analyzed through descriptive quantitative and qualitative methods. The findings indicate that the implementation of the TTW model was systematic, active, and collaborative, significantly enhancing students’ critical reasoning and writing performance, with average scores rising from 62.14 to 83.89. These results support Vygotsky’s theory of social constructivism, which highlights the role of social interaction in knowledge construction, and broaden the understanding of deep learning approaches at the primary level. The study concludes that collaboration in thinking, speaking, and writing serves as a critical strategy for developing students’ reasoning capacity and literacy skills. The implications extend to strengthening constructivist theory in the context of literacy education and provide practical guidance for teachers in designing active, learner-centered instruction. Additionally, the study opens avenues for further exploration of visual media and contextual worksheets in fostering 21st-century competencies in primary education.